PUBLIC PRIVATE PARTNERSHIP AS MEANS OF OVERCOMING ENTRY BARRIERS FOR PRIVATE INVESTORS TO A MARKET OFINFRASTRUCTURE PROJECTS - D. Maximov (Вестник университета)
The definition of Public Private Partnership is given in the article. The major entry barriers for private investors are concerned. Influence of Public Private Partnership development process is analyzed.